Investigation of Acoustic Impedance and Morphology of Vacuum-Thermally Evaporated Polypyrrole Layer and Its Potential for Quartz Crystal Microbalance Sensor - Yudyanto, Yudyanto; Masruroh, Masruroh; Santjojo, Dionysius J.D.H.; Sakti, Setyawan P.; Wardoyo, Arinto Yudi Ponco (Trends in Sciences, 2025)
This study investigated the influence of the morphology of a polypyrrole (PPy) functional layer on the acoustic impedance and PPy-QCM characteristics. In this study, the PPy thin layer was deposited on 1 side of QCM, following the dimension of the Au electrode. The layer production method yielded a simple design of a PPy-functionalized QCM. The impedance and PPy-QCM characteristics were determined by impedance analysis and microscopic observation. A vacuum thermal evaporation technique was used to deposit the PPy layer on the top of the QCM, allowing vertical platelet structure formation. Scanning Electron Microscope (SEM) images suggested that the deposition time increased the sizes of PPy but maintained their shapes. Analysis of impedance consisting of the conductance, bandwidth, and resonance frequency showed that changes in the layer morphology structure increased the resistance and the bandwidth (increasing energy dissipation and viscoelastic properties). As the deposition time increased from 10 to 50 s, the frequency shift experienced a significant increase from 6,000 to 32,000 Hz. This treatment also enlarged the bandwidth from 82 to 470 Hz. In addition, the impedance and load of QCM increased from 5.75 to 27.19 W and from 0.403 to 21.441 W, respectively. However, the deposition time in this range did not alter the stiffness properties of the layer. In other words, the thin PPy layer that was produced remained non-viscoelastic. The overall analyses in this study suggested that the PPy thin layer is promising for QCM sensing applications. HIGHLIGHTS Vacuum evaporation deposited polypyrrole consists of vertical platelet structures. Morphological changes of platelets in the layer are controlled by deposition time. The platelets’ shape and size determine the PPy-QCM impedance and characteristics. Analysis was carried out by impedance spectroscopy and electron microscopy. GRAPHICAL ABSTRACT